Pengaruh Kualitas Pelayanan, Promosi, Lokasi, Fasilitas Dan Harga Terhadap Kepuasan Pasien Di Klinik Dokter Gigi Budhi Jember - Richa Aprilia; Haifa Haifa; Saiful Amin (CV. ITTC INDONESIA, 2025)
The research aim to examine the influence of Service Quality, Promotion, Location, Facility, price on patient satisfaction at the Klinik Dokter gigi Budhi Jember. Patient satisfaction is an important factor in maintaining loyalty and improving the clinic's image in the midst of increasingly fierce health service competition. This study uses quantitative methods, with data collection techniques through distributing questionnaires to 60 respondents who are patients of Klinik Dokter Gigi Budhi Jember. Data analysis was carried out using multiple linear regression with the help of SPSS software version 29. The results showed that promotion and price have a positive influence on patient satisfaction. However, the variables of service quality, location and facilities did not show a significant effect. This indicates that although aspects such as service, location, and facilities contribute to patient experience, patient perceptions of attractive promotions and affordable prices are more instrumental in shaping overall satisfaction in the context of health services at dental clinics.